Calculation of higher heating values of fatty acids. Issue 18 (16th September 2016) - Demirbas, Ayhan
ABSTRACT: Vegetable oils and animal fats comprise of triglycerides which are formed by fatty acids. Some fatty acids, particularly those having the unsaturated bond are not easy to purify. For this reason, it is not possible to determine exactly the higher heating values (HHVs) of unsaturated fatty acids experimentally via the correct way. HHVs of fatty acids can be determined based on carbon (C), hydrogen (H), and oxygen (O) contents in their chemical formula, experimentally HHVs can be determined relatively easily by using common laboratory equipment. The HHVs (MJ/kg) of the fatty acids as a function of percentages of the C, H, and O can be calculated from: According to this equation, the HHV is a function of the percentages of the C, H, and O of the dry and ash-free basis (daf). This equation represents the correlation obtained by means of regression analysis. It is found that the calculated values show mean difference of 0.30%. The correlation coefficient is 0.9917.